Community-Driven Development : Myths and Realities - Wong, Susan (World Bank, Washington, DC, 2018)
Community-driven development is an approach to development that emphasizes community control over planning decisions and investment resources. Over the past decade, it has become a key operational strategy for many national governments, as well as for international aid agencies, with the World Bank alone currently supporting more than 190 active community-driven development projects in 78 countries. Community-driven development programs have proven to be particularly useful where government institutions are weak or under stress. This paper examines what the evidence shows about the utility of community-driven development programs for helping governments improve the lives and futures of the poor. The paper also addresses recent critiques of the community-driven development approach. The paper makes three main arguments. First, community-driven development offers governments a useful new tool for improving the lives of the poor. The empirical evidence from evaluations confirms that community-driven development programs provide much needed productive economic infrastructure and services at large scale, reasonable cost, and high quality. They also provide villagers, especially the disadvantaged, with a voice in how development funds are used to improve their welfare. Second, community-driven development programs are not a homogeneous category, and it is important to acknowledge the differences between national, on-budget, multi-year programs, and off-budget programs. And finally, community-driven development works best and achieves the greatest results when it is part of a broader development strategy that includes reforms to governance, investments in productivity, and integration with efforts to improve the quality of public service delivery.